Shall We Play A Game? Examining the Influence of a Play-Based Learning Approach Using LEGO Bricks on Higher Education Students’ Perception of Academic Stress and Continuation Intention - Jie Min Ho; Ivy Siaw Hung Hii; Qian Hui Ting; Fayrene Yew Leh Chieng; Ka Yii Yip (Tecno Scientifica Publisher, 2026)
Academic stress and student retention are pressing concerns in higher education. This study investigates the impact of a play-based learning (PBL) pedagogy, utilizing LEGO bricks and the Brickit mobile application, on students’ self-perceived academic stress and their intention to continue engaging with such methods. A quasi-experimental activity was conducted with 105 commerce undergraduates. Following the activity, 100 participants completed a cross-sectional survey measuring their evaluation of the PBL approach, perceived academic stress, and continuation intention. Regression analysis revealed that a positive evaluation of the PBL approach was a significant predictor of lower perceived academic stress (β = 0.355, p < 0.001) and higher continuation intention (β = 0.174, p < 0.01). The findings suggest that integrating playful, hands-on elements into curricula can create a more engaging and less stressful learning environment, potentially fostering greater student persistence. This study supports the adoption of innovative, experiential pedagogies to address well-being and engagement challenges in tertiary education.